2013
DOI: 10.1152/ajplung.00133.2012
|View full text |Cite
|
Sign up to set email alerts
|

ADAM15 deficiency attenuates pulmonary hyperpermeability and acute lung injury in lipopolysaccharide-treated mice

Abstract: Sun C, Beard RS Jr, McLean DL, Rigor RR, Konia T, Wu MH, Yuan SY. ADAM15 deficiency attenuates pulmonary hyperpermeability and acute lung injury in lipopolysaccharide-treated mice. Am J Physiol Lung Cell Mol Physiol 304: L135-L142, 2013. First published November 16, 2012 doi:10.1152/ajplung.00133.2012.-ADAM15 is a disintegrin and metalloprotease recently implicated in cancer and chronic immune disorders. We have recently characterized ADAM15 as a mediator of endothelial barrier dysfunction. Whether this molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…In contrast, leukocyte-expressed ADAM 10 but not ADAM 17 displays proinflammatory activities and may therefore serve as a target to limit inflammatory cell recruitment (114). Sun and colleagues (134) showed that ADAM 15 is activated during lung injury and disrupts endothelial barrier function and induces neutrophil infiltration. Therefore, LPS failed to induce inflammatory injury in ADAM 15 knockout mice.…”
Section: Endothelial Scaffoldsmentioning
confidence: 99%
“…In contrast, leukocyte-expressed ADAM 10 but not ADAM 17 displays proinflammatory activities and may therefore serve as a target to limit inflammatory cell recruitment (114). Sun and colleagues (134) showed that ADAM 15 is activated during lung injury and disrupts endothelial barrier function and induces neutrophil infiltration. Therefore, LPS failed to induce inflammatory injury in ADAM 15 knockout mice.…”
Section: Endothelial Scaffoldsmentioning
confidence: 99%
“…Modulatory roles of integrins are well established in acute lung damages [70]. Similarly, aberrant expression of genes involved in integrin signaling can also provoke acute lung injuries, namely-ADAM15 [71], SDC1 [72], CD14 [73], CD47 [74], CD9 [75], HMGB1 [76], ITA6 [77], and ITAV [78] etc. Therefore, SARS-CoV-2 infection induced deregulation of these genes might be contributing towards the worsening of the normal pathobiology and functionality of lungs in COVID-19.…”
Section: Inflammatory Immune Responses Were Several Folds Higher In Lmentioning
confidence: 99%
“…No major pathologies. Reduced neutrophil chemotactic transmigration across, attenuated pulmonary inflammatory response [177], faster development of osteoarthritis [178] ADAM17 Knock-out: Perinatal lethality [162], eyelid, hair, skin, lung development and heart valves defects [179,180]. Gene knock-down: eye, heart, skin defects, increased vulnerability to inflammation in DSS colitis [181].…”
Section: Adam15mentioning
confidence: 99%